2015
DOI: 10.1103/physreve.91.022922
|View full text |Cite
|
Sign up to set email alerts
|

Delay-induced remote synchronization in bipartite networks of phase oscillators

Abstract: We study a system of mismatched oscillators on a bipartite topology with time-delay coupling, and analyze the synchronized states. For a range of parameters, when all oscillators lock to a common frequency, we find solutions such that systems within a partition are in complete synchrony, while there is lag synchronization between the partitions. Outside this range, such a solution does not exist and instead one observes scenarios of remote synchronization-namely, chimeras and individual synchronization, where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Equation (30) shows that the number of overlaps m increases linearly with n. As noted above, we have r" = htt/ cd e /". Therefore, the number of coexisting stable synchronized solutions increases essentially linearly with increasing mean delay r and grows unbounded [cf.…”
Section: Multistability Of Synchronized Solutions In Kuramoto Osmentioning
confidence: 87%
“…Equation (30) shows that the number of overlaps m increases linearly with n. As noted above, we have r" = htt/ cd e /". Therefore, the number of coexisting stable synchronized solutions increases essentially linearly with increasing mean delay r and grows unbounded [cf.…”
Section: Multistability Of Synchronized Solutions In Kuramoto Osmentioning
confidence: 87%
“…Apart from their application to a variety of physical [3,4] and biological [5,6] situations, the robustness of such complexity has attracted considerable recent interest. Earlier studies have suggested that in order to observe chimera states, some degree of nonuniformity is essential [7], and this nonuniformity can arise due to heterogeneities in the coupling [1,[8][9][10], in the topology [11,12], parameters [13][14][15], or by allowing for amplitude variation [16]. It has also been seen that time-delay coupling can cause nonuniformity, although it is possible that chimera states reported in several theoretical studies are long transients [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…A solution of this type is termed a splay phase and known to occur in a variety of dynamical systems; this is the generalisation of the anti-phase solution that occurs in the bipartite system [21,22]. Apart from these generic solutions, existing for all values of τ , there can be other phase locked solutions as well, and these can be calculated on a case-by-case basis, depending on the number of partitions in the network and the parameters ε and τ .…”
Section: Phase Oscillators On a K−partite Networkmentioning
confidence: 99%
“…Notice that there is a range of values of τ where there is only a single stable state, as well as parameter ranges when there are several stable frequencies [18]. The width of this latter range increases with increasing coupling strength [21].…”
Section: Phase Oscillators On a K−partite Networkmentioning
confidence: 99%
See 1 more Smart Citation